Non-verbal cues as a test of gender and race bias in politics: the Italian case. (1st July 2015) - Iyengar, Shanto; Barisione, Mauro
Introduzione: Gender and race biases persist in western democracies, with male and white candidates still being the norm. Voters may be more inclined to express sexist and racist attitudes in countries with a traditionally male-dominated political system and a majority-white population. As sexism and racism are notoriously difficult to document, and because many people are unaware of their biases toward social groups, we bypass conventional survey measurement and observe voters' willingness to support candidates whose physical features have been manipulated to make them appear more prototypically feminine or non-white. We implemented this approach in the context of the 2013 Italian election, by presenting a national sample of Italian voters with pictures of male and female parliamentary candidates – both unknown and well known. Overall, we found no main effects of gender or race bias in political judgment. For Italian voters, party cues are by far the most powerful indicators of out-group status, and therefore the strongest predictors of candidate perception and support. This result may be of particular interest to other political contexts characterized by strong partisan polarization.